Do Woman On Boards, Size Of Boards, And CEO Characteristics Affect Sustainability Performance? - Amaliani, Shofi Nur; Cahya, Bayu Tri; Ilyas, Rahmat; Salsabila, Sekar Rani; Nurjati, Fawzia Zakisa (Fakultas Ekonomi dan Bisnis, Universitas 17 Agustus 1945 Surabaya, 2024)
Sustainability performance is critical for companies to balance the interests of all stakeholders that contribute to the company's current and future success through sustainable value creation that satisfies shareholders and other stakeholders over the long term. Several factors can influence sustainability performance. This study aims to analyze the impact of women on boards, board size, and CEO characteristics on the sustainability performance of companies in the health sector listed on the Indonesian Sharia Stock Index for 2019-2022. This research is quantitative. The results of this study indicate that women on boards, the size of boards, and the age of the CEO affect sustainability performance. While CEO education, CEO nationality, and narcissism do not affect sustainability performance. Keywords: Sustainability performance, Women on boards, size of the board, CEO characteristics